Effectiveness of Cash Assistance (BLT) for Communities Affected by The Pandemic Covid-19: Case study in Sirnajaya village, Cibadak sub-district, Sukabumi district - Kantirina Rachaju (IHSA Institute, 2021)
The Pandemic Covid-19 not only has an impact on health, but also has an impact on social and economic conditions. The social and economic impacts caused by the Pandemic Covid-19 are very influential on the level of community welfare, while the purpose of this paper is to find out and understand the effectiveness of the distribution of government programs, namely Direct Cash Assistance in the Sirnajaya Village area and the implementation of the Family Hope Program distribution in Cibadak District, Sukabumi, West Java. , as well as explaining any problems that could hinder the distribution of the aid. The COVID-19 outbreak has hit many business sectors, resulting in layoffs, and reducing employment. Given the high mobility. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the Indonesian government has carried out various efforts to deal with the pandemic. Various policies have been formulated to protect vulnerable people who are also affected by the Pandemic Covid-19 through social assistance policies provided by the government, which are expected to be able to help the poor affected by COVID-19 to continue to carry out their lives, such as the distribution of Direct Cash Assistance that occurred in the Sirnajaya Village area, District. Sukabumi, in this case the village government through village funds has carried out its functions in accordance with central government regulations, namely empowering the Sirna Jaya village community by maximizing the direct cash assistance for daily needs, although in the process there are still some problems that need to be resolved so that the distribution of the Cash Direct Assistance program can be well absorbed according to the predetermined targets.